Tse1 mobilized by T6SS of Pseudomonas induces sporulation of Bacillus via σW - Pérez-Lorente, Alicia; Molina-Santiago, Carlos; De-Vicente-Moreno, Antonio; Romero, Diego (My University, 2022)
The extracellular matrix and sporulation are defensive mechanisms used by Bacillus cells when they interact with Pseudomonas strains expressing a type VI secretion system (T6SS). Here, we define Tse1 as the main toxin mobilized by the Pseudomonas T6SS that triggers sporulation in Bacillus. We characterize Tse1 as a peptidoglycan hydrolase and electron microscopy analysis and the use of diverse chemical probes, let us visualize malfunction of the Bacillus cell membrane. By performing RNA-seq and immunocytochemistry analyses, we also delineate the response of Bacillus cells to Tse1, which through the coordinated actions of the extracellular sigma factor σW and the cytoplasmic histidine kinases KinA and KinB, culminates in activation of the sporulation cascade. We propose that this cellular developmental response is conserved in Bacilli to defend against the toxicity of T6SS-mobilized Tse1 effector.
Keywords: Bacillus (Bacteria); Bacillus; T6SS